A battery separator and its preparation method and application
Patent Information
- Application Number
- CN202611280972.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-24
- Publication Date
- 2026-10-30
AI Technical Summary
[0010]本发明针对现有的锂电池隔膜在长期循环中因“界面副反应物污堵”与“极片膨胀物理挤压”双重作用导致的孔隙堵塞、离子通道退化、透气值激增以及由此引发的负极析锂和容量快速衰减等技术问题,本发明提供一种电池隔膜及其制备方法和应用
[0043](1)长期循环中电解液持续分解产生污堵物,孔壁纳米颗粒B凭借其低表面能特性实现物理排斥,使污堵物无法在通道内壁固化堆积。面向负极侧的纳米颗粒 A诱导并调控负极表面电化学行为,原位形成富含无机物的致密高韧性 SEI 膜,自钝化负极界面、阻止电解液进一步接触负极,从化学源头阻断有害副产物的持续生成。发明通过构筑一种集“物理排斥”与“化学稳定”于一体的双重主动防护机制,维持长期循环中隔膜内部离子传输网络的长期畅通。
Smart Images

Figure CN123018356A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of batteries, specifically relating to a battery separator, its preparation method, and its applications. In particular, it relates to functionalized composite separators for lithium-ion batteries used in long-cycle, long-life applications such as high-energy-density, high-nickel ternary / silicon-carbon systems. Background Technology
[0002] During long-term cycling of lithium-ion batteries (especially high-energy-density batteries), continuous interfacial side reactions and electrode volume expansion constantly compress and clog the pores of the separator. Existing ceramic-coated separators or polymer monolayer-coated separators mainly focus on improving the thermal shrinkage performance of the separator or improving its wettability with the electrolyte, lacking a targeted design for the problem of "dynamic pore degradation during cycling," and exhibiting the following serious defects when facing long-term cycling:
[0003] During long-term charge-discharge cycles of high-energy-density lithium-ion batteries, the complex electrochemical evolution and mechanical changes within the battery continuously damage the microporous structure of the separator, leading to dynamic pore degradation. This problem is particularly prominent in high-expansion battery systems such as silicon-based anodes. On the one hand, the dramatic volume expansion and contraction effects of novel anode materials like silicon-based anodes during charge-discharge cycles exert continuous and periodic mechanical pressure on the separator, causing the micropores to deform, collapse, or even close under pressure. On the other hand, the electrode interface in high-energy-density battery systems is more active, and the electrolyte is prone to continuous side reactions at the anode interface, generating byproducts such as organic polymers and inorganic salts. These solid byproducts continuously deposit and embed themselves within the separator pores, causing irreversible physical blockage of the micropores. The combined effect of these two negative effects continuously compresses and blocks the separator pores, disrupting the original uniform porous ion transport network of the separator, becoming a core bottleneck restricting the stable operation of high-energy-density lithium-ion batteries during long cycles.
[0004] The dynamic degradation of the separator's pore structure triggers a series of cascading electrochemical failures. As pore compression deformation and blockage intensify, the separator's permeability (Gurley value) increases significantly, drastically reducing the lithium-ion transport channels within the separator and drastically decreasing connectivity. This directly leads to a substantial increase in lithium-ion transport resistance and causes severe uneven distribution of ion flow within the battery. This uneven ion flux disrupts lithium-ion deposition behavior on the negative electrode surface, inducing severe lithium plating. The generated lithium dendrites not only continuously consume active lithium, accelerate battery capacity decay, and disrupt the battery's internal electrochemical balance, but also easily puncture the separator, causing major safety hazards such as micro-short circuits and thermal runaway, significantly reducing the lifespan and safety redundancy of high-energy-density lithium-ion batteries.
[0005] Currently, there has been much research on modification technologies for lithium-ion battery separators in the industry. The mainstream modification schemes include ceramic-coated separators, polymer monolayer coated separators, solid electrolyte composite separators, and low surface energy modified separators. Although various modified separators have achieved certain optimizations in a single performance dimension, none of them have been specifically designed to address the core pain point of dynamic degradation of separator pores during long-term battery cycling. They cannot effectively solve the problems of pore blockage and ion transport network failure under long-term cycling, and have significant technical limitations.
[0006] Conventional single-ceramic coated separators typically use inorganic ceramic particles such as alumina and boehmite for surface coating. The core purpose of their modification is to improve the separator's high-temperature resistance, shrinkage resistance, and electrolyte wettability, ensuring basic battery safety and wettability. However, the pore walls of this type of separator exhibit high surface energy and hydrophilic properties. During battery cycling, they actively adsorb various byproducts generated by electrolyte decomposition, accelerating the deposition and embedding of these byproducts within the pores. They completely lack active anti-fouling capabilities and cannot inhibit dynamic pore degradation. After long-term cycling, problems such as pore blockage and impaired ion transport still occur.
[0007] Existing solid-state electrolyte composite membranes (such as the LLZTO / LATP-coated solid-state electrolyte membrane described in patent CN108878751B) generally adopt a modification approach of homogeneous dispersion of solid-state electrolytes. The focus of technological development is on improving the room-temperature ionic conductivity of the membrane to optimize battery rate performance. However, existing solutions suffer from core design deficiencies. They fail to utilize the solid-state electrolyte to construct backup ion transport pathways after pores are closed under pressure, thus failing to address transport failures caused by pore mechanical collapse. Furthermore, they do not leverage the interfacial properties of the solid-state electrolyte to achieve in-situ regulation of the electrochemical behavior at the negative electrode interface, making it difficult to alleviate interfacial side reactions and pore blockage problems. Consequently, their effectiveness in improving the long-cycle stability of batteries is very limited.
[0008] Furthermore, the application scenarios of existing low surface energy membrane modification technologies are relatively limited, mostly concentrated in conventional fields such as water filtration and waterproofing, and have not yet been specifically adapted to the electrochemical cycling conditions of lithium-ion batteries. They cannot achieve the repulsion and blockage of electrolyte decomposition byproducts through optimization of the pore wall interface characteristics, nor can they inhibit the pore deposition of byproducts at the source, making it difficult to solve the industry pain point of dynamic pore degradation of the membrane during long-term cycling.
[0009] In summary, existing modified separator technologies all suffer from design flaws, lacking systematic solutions to address the dynamic degradation of separator pores, ion transport network failure, lithium plating at the negative electrode, and lifespan decline during long-cycle operation of high-energy-density batteries. They fail to simultaneously meet the requirements of separator resistance to pore blockage, stable ion transport, suppression of lithium plating, and long-term safe operation, significantly limiting the improvement of cycle performance and safety in high-energy-density lithium-ion batteries. Therefore, developing a novel separator that is adaptable to high-expansion negative electrode systems and possesses long-term resistance to pore degradation, stable ion transport, and suppression of lithium plating at the negative electrode has become a pressing technical problem to be solved in this field. Summary of the Invention
[0010] This invention addresses the technical problems of existing lithium-ion battery separators during long-term cycling, including pore blockage, ion channel degradation, and a surge in permeability caused by the combined effects of interfacial byproduct contamination and electrode expansion and physical compression. The invention provides a battery separator, its preparation method, and its applications. The battery separator of this invention employs a composite configuration of a base film and a multifunctional gradient coating. The multifunctional gradient coating has a gradient pore size structure that gradually changes along the thickness direction, and the coating interior is uniformly loaded with two complementary nanoparticles (low surface energy selective anti-adsorption nanoparticles B and solid ion conductor particles A), which can maintain the long-term unobstructed ion transport network inside the separator during long-term cycling.
[0011] To address the aforementioned technical problems, the first aspect of the present invention provides a battery separator, the battery separator comprising a base film and a multifunctional gradient coating formed on at least one surface of the base film, wherein the multifunctional gradient coating comprises a stacked bottom coating A and a top coating B, wherein the bottom coating A contains solid ion conductor nanoparticles A, the top coating B contains nanoparticles B, and the pore size of the top coating B is larger than the pore size of the bottom coating A; the nanoparticles B are inorganic particles and / or polymer microparticles with low surface energy.
[0012] In this invention, the surface coating B has a relatively large pore size, providing mechanical elastic space to buffer the volume expansion of the negative electrode and preferentially accommodating the deposition of trace by-products generated in the early stages of cycling, thus acting as a "sacrificial buffer." The bottom coating A has a relatively dense structure, serving as the main ion channel and maintaining long-term interface stability and anti-fouling ability. The gradient pore size structure that gradually changes along the thickness direction can significantly reduce the problems of pore blockage and ion channel degradation. A schematic diagram of the battery separator structure of this invention is shown below. Figure 1 As shown.
[0013] In this invention, the particle size of nanoparticle A is larger than that of nanoparticle B. In this invention, nanoparticle A forms a dynamic ion flow control layer. Nanoparticle B forms a low surface energy anti-adsorption layer.
[0014] In this invention, the average particle size D of the nanoparticle A is... 50 The average particle size D of nanoparticle A is 250nm-500nm. 50 For example, but not limited to 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, and any value between any two values. When the negative electrode expands violently, causing local coatings to be squeezed under high pressure and some pores to close, the uniformly dispersed nanoparticles A form a continuous solid-state ion transport network that runs through the thickness direction within the coating. This network serves as a redundant backup conduction path to dynamically compensate for the obstructed area and redistribute the ion flow, ensuring that the local lithium ion flow remains uninterrupted and uniform even when the porosity decreases.
[0015] In this invention, the average particle size D of the nanoparticle B is... 50 The average particle size D of nanoparticle B is 100nm-200nm. 50 The values are 100nm, 150nm, 200nm, and any value between any two. In this invention, during long-term cycling, the electrolyte continuously decomposes to produce contaminants. The surface nanoparticles B, due to their low surface energy, achieve physical repulsion, preventing the contaminants from solidifying and accumulating on the inner wall of the channel.
[0016] In this invention, the nanoparticle A is selected from garnet-type solid electrolytes and / or NASICON-type solid electrolytes; preferably, the nanoparticle A is selected from one or more of LLZTO, LATP, and LAGP; more preferably, the ionic conductivity of the nanoparticle A at room temperature is ≥1×10⁻⁶. -4 S / cm. This invention employs solid-state ion-conducting nanoparticles A with lithium-ion conductivity, which are distributed in the coating at a permeable concentration to form a continuous ion transport network spanning the coating thickness, thereby undertaking the dual functions of "dynamic ion flow reconstruction" and "in-situ regulation of the negative electrode interface". The essential limitation of nanoparticle A in this invention lies in its functional mechanism, namely: when the coating porosity decreases due to compression / fouling, the continuous solid-state ion network composed of nanoparticles A acts as a redundant pathway to dynamically compensate for the obstructed area, ensuring that the ionic conductivity of the membrane is still not lower than 70% of its initial value.
[0017] In this invention, the surface free energy of the nanoparticles B is ≤25 mN / m; preferably, the low surface free energy of the nanoparticles B is imparted by the chemical composition of the grafted modified layer, or is inherent in the chemical composition of the framework material of the nanoparticles B themselves; more preferably, the nanoparticles B are selected from one or more of fluorinated or alkylated Al2O3, fluorinated or alkylated SiO2, fluorinated or alkylated TiO2, PTFE (Polytetrafluoroethylene) based microparticles, fluorinated polyether microparticles (PFPE, Perfluoropolyether), and fluorinated or alkylated ZrO2. This invention uses low surface energy modified nanoparticles (surface free energy ≤25 mN / m) to form a selective anti-adsorption interface against by-reaction products on the pore walls. These particles are embedded in the inner walls of the coating pores, forming a microscopic low surface energy "non-stick" surface that repels solid / semi-solid by-products generated by electrolyte decomposition, preventing their physical adhesion and accumulation within the pores.
[0018] In this invention, the bottom coating A contains a first polymer matrix and nanoparticles A. Preferably, based on the total weight of the bottom coating A, the content of the first polymer matrix is 50-90% by weight (e.g., 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%), and the content of nanoparticles A is 10-50% by weight (e.g., 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%). In this invention, the first polymer matrix has a relatively high proportion in the solid phase, forming a dense main ion channel layer with small pore size after curing.
[0019] In this invention, the first polymer matrix is selected from one or more of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), and polyacrylic acid resin. This invention employs a polymer matrix with excellent electrochemical window and adhesive properties, preferably polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP).
[0020] In this invention, the surface coating B comprises a second polymer matrix, nanoparticles B, and optionally nanoparticles A. Preferably, based on the total weight of the surface coating B, the content of the polymer matrix is 20-50% by weight (e.g., 20%, 25%, 30%, 35%, 40%, 45%, 50%), the content of nanoparticles B is 20-70% by weight (e.g., 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%), and the content of nanoparticles A is 0-45% by weight. In this invention, the low surface energy anti-adhesion principle of the "lotus effect" is used to modify the inner wall of the diaphragm pores. By optimizing the interfacial characteristics of the pore inner wall, the decomposition byproducts of the electrolyte are repelled and blocked, inhibiting the deposition of byproducts in the pores from the source and solving the problem of dynamic degradation of diaphragm pores during long-term cycling. Furthermore, the introduction of solid-state ion-conducting nanoparticles A can construct a continuous or semi-continuous lithium-ion fast transport network within the surface coating, improving the local ion conductivity of the separator, shortening the lithium-ion transport path across the separator, and reducing ion migration impedance and concentration polarization. When local pores are partially blocked due to the deposition of a small amount of by-products, the solid-state ion-conducting nanoparticles A can still provide additional ion transport channels, maintaining the effective ion flux of the separator, reducing local current density concentration, and promoting uniform lithium-ion deposition, thereby further suppressing lithium plating and dendrite growth, and improving the battery's long-cycle capacity retention and rate performance.
[0021] In this invention, the second polymer matrix is selected from one or more of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), and polyacrylic acid resin. This invention employs a polymer matrix with excellent electrochemical window and adhesive properties, preferably polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP).
[0022] In this invention, based on the total weight of the battery separator, the total content of the first polymer matrix and the second polymer matrix is 30-50% by weight (e.g., 30%, 35%, 40%, 45%, 50%), the content of nanoparticle B is 10-40% by weight (e.g., 10%, 15%, 20%, 25%, 30%, 35%, 40%), and the content of nanoparticle A is 20-50% by weight (e.g., 20%, 25%, 30%, 35%, 40%, 45%, 50%), and the content of nanoparticles in the surface coating B is greater than the content of nanoparticles in the bottom coating A. Within the above content range, the battery separator exhibits better physical repulsion and anti-fouling properties and dynamic ion flow reconstruction pathways.
[0023] In this invention, the weight ratio of nanoparticle B to nanoparticle A is 1:0.5-3. For example, but not limited to, ratios of 1:0.5, 1:1, 1:1.5, 1:2, 1:3, etc. In this invention, if the weight ratio of nanoparticle B to nanoparticle A is too low, the anti-fouling effect will be insufficient; if it is too high, the continuity of the backup ion pathway will decrease. This preferred ratio ensures that both the "draining" and "conducting" functions achieve permeation simultaneously on the pore wall.
[0024] In this invention, the thickness ratio of the base film, the bottom coating A, and the top coating B is 1:0.1-0.5:0.1-0.7, preferably 1:0.1-0.3:0.1-0.4. Examples, but not limited to, are 1:0.15:0.25, 1:0.2:0.3, 1:0.3:0.45, 1:0.4:0.5, 1:0.5:0.7, etc. This thickness ratio provides a superior gradient elastic buffering effect.
[0025] In this invention, the base film is preferably a wet-process biaxially oriented polyethylene single-layer film or a PE / PP / PE multilayer composite film; preferably, the thickness of the base film is 5μm-12μm. The combination of a high-strength base film and a multifunctional gradient coating results in a battery separator with superior performance.
[0026] In this invention, after 1000 1C charge / discharge cycles, the air permeability value B of the battery separator, relative to the air permeability value A before the cycles, has a change ratio B / A ≤ 1.2. The separator of this invention, through a synergistic design of "physical repulsion" and "dynamic ion flow reconstruction," effectively prevents channel blockage and compression closure. The internal lithium-ion transport network of the separator is complete, achieving a long-term uniform distribution of ion flow and fundamentally suppressing lithium plating at the negative electrode.
[0027] In this invention, the multifunctional gradient coating faces the negative electrode side. In the prior art, the dramatic volume expansion of the negative electrode (especially silicon-based negative electrodes) during cycling directly exerts mechanical pressure on the separator; simultaneously, the electrolyte undergoes continuous interfacial side reactions under the catalysis of a highly active negative electrode, and the resulting byproducts (such as organic polymers, inorganic salts, etc.) gradually deposit and embed themselves inside the separator pores, causing irreversible physical blockage. Locally uneven lithium-ion flow triggers severe lithium plating on the negative electrode surface, forming lithium dendrites, which not only damage the electrochemical network and accelerate capacity decay, but also puncture the separator, posing a serious safety hazard. The multifunctional gradient coating of this invention can actively regulate the negative electrode interface, in-situ inducing the formation of a dense and stable inorganic-enriched SEI film, suppressing side reactions and reducing the total amount of byproducts from the chemical source. At the same time, this invention utilizes the elastic structure of the gradient pores to effectively buffer the local stress concentration caused by the volume expansion of the negative electrode. Therefore, when assembling the battery, the multifunctional gradient coating is preferably configured facing the negative electrode side.
[0028] In this invention, the coating on the positive electrode side is not limited. In a preferred embodiment, the coating facing the positive electrode is preferably formulated according to the composition listed in Example 3 of this invention. When the formulation of Example 3 is used as the coating facing the positive electrode, the membrane performance can be effectively improved.
[0029] In this invention, the coating facing the positive electrode has a total content of 40-55% by weight of the first polymer matrix and the second polymer matrix, and a content of 45-60% by weight of nanoparticle A, based on the total weight of the positive electrode side diaphragm.
[0030] The types of the first polymer matrix, the second polymer matrix, and nanoparticle A are the same as those in the coating of the battery separator facing the negative electrode side described above.
[0031] A second aspect of the present invention provides a method for preparing the above-mentioned battery separator, the method comprising:
[0032] S1. Apply the undercoating slurry A to at least one surface of the base film and perform a first drying to obtain a base film with the undercoating A.
[0033] S2. A topcoat slurry B is applied to the surface of the base film with the bottom coating A obtained in S1, followed by a second drying. In this invention, the gradient coating is constructed through a step-by-step continuous coating process. That is, on the same continuous coating production line, two or more slurries with different compositions are successively coated onto the surface of the base film by independently metered multi-pass coating units. Each subsequent slurry is applied after the previous coating has been dried and formed, resulting in a multifunctional gradient coating in which the pore size and composition gradient along the thickness direction can be independently designed.
[0034] According to the method of the present invention, the conditions for the first drying include: a temperature of 50-90°C and a time of 0.2-2 hours. In the present invention, the first drying can solidify the surface coating slurry A to form a dense main ion channel layer with small pore size.
[0035] According to the method of the present invention, the second drying conditions include: raising the temperature to 50-70°C and holding for 30-120 seconds, then raising the temperature to 70-90°C and holding for 1-5 minutes. The solvent gradient is first removed and the particle distribution is locked in the pre-drying / setting temperature zone of 50-70°C, and then thoroughly cured in the complete drying temperature zone of 70-90°C. Finally, the film is wound up to obtain a multifunctional gradient coating membrane with a "dense inside and sparse outside".
[0036] According to the method of the present invention, the undercoating slurry A contains a first polymer matrix, nanoparticles A, solvent A, and optionally a pore-forming agent A. Preferably, the weight ratio of the first polymer matrix, nanoparticles A, solvent A, and optionally pore-forming agent A is 1:0.1-1.2:3-10:0-0.3, more preferably 1:0.1-1.1:3-8:0-0.3. In the present invention, an undercoating slurry A with a high polymer content and containing no or very little pore-forming agent is prepared. Within this ratio range, the polymer matrix accounts for a relatively high proportion in the solid phase, and after curing, a dense main ion channel layer with small pore size is formed.
[0037] According to the method of the present invention, the surface coating slurry B contains a second polymer matrix, nanoparticles B, solvent B, pore-forming agent B, and optionally nanoparticles A; preferably, the weight ratio of the second polymer matrix, nanoparticles B, solvent B, pore-forming agent B, and optionally nanoparticles A is 1:0.5-3:3-20:0.3-1.5:0-3, more preferably 1:0.5-2.2:8-20:0.5-1.3:0-2. In the present invention, a surface coating slurry B with low polymer content and the introduction of a pore-forming agent (such as deionized water or other non-solvent or volatile / extractable pore-forming components) is prepared, within a preferred proportion range, and the total proportion of functional particles is higher than that of slurry A, forming a buffer layer with larger pore size and high elasticity after curing. Here, deionized water is used as a non-solvent pore-forming agent for PVDF-HFP: water does not dissolve PVDF-HFP but is miscible with NMP. During the coating drying process, it induces local phase separation and precipitation of PVDF-HFP to form pores. After the water evaporates, it leaves larger pores in situ.
[0038] According to the method of the present invention, pore-forming agent A and pore-forming agent B are each independently selected from one or more of deionized water, ethanol, ethylene glycol, polyethylene glycol and glycerol.
[0039] According to the method of the present invention, solvent A and solvent B are each independently selected from one or more of N-methylpyrrolidone (NMP), dimethylacetamide (DMAC), dimethyl sulfoxide (DMSO) and N,N-dimethylformamide (DMF).
[0040] According to a specific embodiment of the present invention, on a continuous coating production line, the first coating unit first coats the bottom coating slurry A onto the surface of the base film facing the negative electrode side, and then dries it to form the bottom coating slurry A; subsequently, the second coating unit coats the top coating slurry B onto the formed bottom coating A.
[0041] A third aspect of the present invention provides a battery comprising the battery separator described above and / or a battery separator prepared by the method described above.
[0042] The beneficial effects of this invention are:
[0043] (1) During long-term circulation, the electrolyte continuously decomposes and generates fouling. The nanoparticles B on the pore wall achieve physical repulsion due to their low surface energy, preventing the fouling from solidifying and accumulating on the inner wall of the channel. The nanoparticles A facing the negative electrode induce and regulate the electrochemical behavior of the negative electrode surface, forming a dense and tough SEI film rich in inorganic matter in situ. This film self-passivates the negative electrode interface and prevents the electrolyte from further contacting the negative electrode, thus blocking the continuous generation of harmful byproducts from the chemical source. The invention maintains the long-term unobstructed flow of the ion transport network inside the membrane during long-term circulation by constructing a dual active protection mechanism that integrates "physical repulsion" and "chemical stability".
[0044] (2) The present invention can significantly reduce the surface energy of the inner wall of the membrane pores and prevent the electrolyte decomposition products from adhering and accumulating inside the pores.
[0045] (3) The battery separator of the present invention can provide a backup solid ion conduction path with high conductivity when the separator pores are mechanically squeezed and the physical channels are blocked.
[0046] (4) The present invention can actively regulate the negative electrode interface and induce the formation of a dense and stable inorganic enriched SEI film in situ, thereby inhibiting side reactions and reducing the total amount of by-products from the chemical source.
[0047] (5) The present invention utilizes the elastic structure of gradient pores to effectively buffer the local stress concentration caused by the volume expansion of the negative electrode.
[0048] (6) The present invention maintains the diaphragm size stability under high temperature / extrusion by constructing an inorganic framework through solid electrolyte and ceramic particles, thereby reducing the risk of internal short circuit.
[0049] (7) When the negative electrode expands violently, causing local coating to be subjected to high pressure and some pores to close, the uniformly dispersed functional particles A form a continuous solid-state ion transport network that runs through the thickness direction within the coating. This network serves as a redundant backup conduction path to dynamically compensate for obstructed areas and redistribute the ion flow, ensuring that the local lithium-ion flow remains uninterrupted and uniform even when the porosity decreases. Preferably, when the coating porosity decreases due to compression / fouling, the ionic conductivity of the separator is still not lower than 70% of its initial value. This achieves interface-level pollution reduction.
[0050] (8) The present invention absorbs the negative electrode expansion stress through the elastic structure of gradient pores, which alleviates the overall compaction of the coating and forms a “prevention-drainage-guidance-mitigation” closed loop with the above three mechanisms. Attached Figure Description
[0051] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0052] Figure 1 This is a schematic diagram of the structure of the battery separator of the present invention.
[0053] Explanation of reference numerals in the attached figures:
[0054] 1-Base film; 2-Underlying coating A; 3-Top coating B. Detailed Implementation
[0055] This invention provides a battery separator, its preparation method, and its application. The invention is further described below with reference to specific embodiments. It should be understood that the following specific embodiments are for illustrative purposes only and are not intended to limit the scope of the invention.
[0056] In the following embodiments, the testing method is as follows:
[0057] (1) Surface free energy test method: Referring to ASTM D7334-08 (2022) and ASTM D7490-08, the Washburn capillary permeation method was used for testing: The particle sample to be tested was passed through an 80~100 mesh sieve, dried and placed in a glass sample tube with filter paper at the bottom. The tube wall was gently tapped to make the powder settle evenly and the column height was recorded. The sample tube was vertically suspended under an electronic balance with an accuracy of 0.1 mg and the lower end was immersed in the test solution. The data of the weight gain m of the sample tube during the permeation process as a function of time t were collected in real time. The linear segment was fitted according to the Washburn equation to obtain the contact angle between the test solution and the particle surface. The test solutions were deionized water and diiodomethane. After obtaining the contact angle of the particle sample relative to deionized water and diiodomethane, the values were substituted into the OWRK model to solve the problem simultaneously, thereby obtaining the surface free energy of the particle.
[0058] (2) Aperture test method: A scanning electron microscope (ZEISS SIGMA300) was used to photograph the cross-section of the coating. Twenty complete holes were randomly selected in the coating A and coating B areas respectively, and the aperture size was measured. The average value was taken to obtain the aperture of coating A and coating B.
[0059] (3) Average particle size test method
[0060] If the raw material is known, the particle size of the nanoparticles is determined according to the national standard GB / T19077-2016 "Laser Method for Particle Size Distribution". Specifically, a laser particle size analyzer (Dandong Baite, BT-2600E) is used, and the dry method is selected for testing. The particles to be tested are fully ultrasonically dispersed into the storage funnel, and about 3 grams of the sample to be tested are added. The feed is turned on for testing, and the pressure is set to about 0.2 MPa. The light-blocking rate is controlled between 8-15%. Three sets of tests are performed, and the average value is obtained, which is the average particle size.
[0061] If the raw material particle size is unknown, cut a 10cm*10cm sample of the diaphragm, fix it to the sample stage with conductive tape, and sputter-coat it with 5-10nm gold to enhance conductivity and prevent charging effects. Use 5kx magnification to photograph the area where the particles are uniformly dispersed. Collect at least 5 different images. Use the length tool on the scanning electron microscope (Zeiss field emission scanning electron microscope, ZEISS SIGMA 300) to measure the major and minor diameters of the particles under image scale calibration. Randomly select 100 clear, non-overlapping particles for measurement. Record the particle size values and calculate the average particle size for both large and small particles. If the particle size of the raw material is unknown, a 10cm*10cm sample of the separator is cut and the battery separator is treated with a diamond cutter or ion polishing to prepare a flat MD-ZD (length-thickness direction) cross-section. The cross-section is observed with a scanning electron microscope (ZEISS SIGMA 300). Image processing tools are used to binarize the cross-sectional SEM image to accurately distinguish between the bottom coating and the surface coating. The image processing tools are used to automatically identify each independent cross-section and calculate the area of the nanoparticles (at least 100 particles are processed), and then convert it into the equivalent circle diameter. All the statistically obtained equivalent circle diameters are substituted into the data table, and volume-weighted conversion is performed to calculate the average particle size of the nanoparticles.
[0062] In the following examples, the raw materials were purchased commercially as follows:
[0063] (1) PVDF-HFP was purchased from Arkema (Shanghai) Chemical Co., Ltd., CAS No. 9011-17-0.
[0064] (2) The preparation method of fluorinated Al2O3 is as follows: high-purity nano-alumina (D 50 Al2O3 with a surface free energy of ≤25mN / m was obtained by dispersing Al2O3 with a surface free energy of ≈100nm and a specific surface area of ≥15m² / g (purchased from Xuancheng Jingrui New Materials Co., Ltd.) in anhydrous ethanol, adding perfluorooctyltriethoxysilane (CAS: 51851-37-7, purchased from Aladdin Reagent (Shanghai) Co., Ltd.), stirring and refluxing at 80℃ for 6h, centrifuging, washing and vacuum drying.
[0065] (3) Nano LLZTO (Li7La3Zr2TaO) 12 Purchased from Jiangsu Jiuwu High-Tech Co., Ltd., D 50 ≈350nm, room temperature ionic conductivity ≥1×10 -4 S / cm, purity ≥99.9%.
[0066] (4) Nano-LATP (Li 1.3 Al 0.3 Ti 1.7 (PO4)3) Purchased from Suzhou Antefi Technology Co., Ltd., D 50 ≈120nm, room temperature ionic conductivity ≥7×10 -4 S / cm, purity ≥99.9%.
[0067] (5) PTFE was purchased from Daikin Industries, Ltd., CAS No. 9002-84-0.
[0068] Preparation Example 1
[0069] Preparation method of alkylated SiO2: High-purity nano-silicon oxide (D... 50 ≈100nm (purchased from Evonik Specialty Chemicals (Shanghai) Co., Ltd.) was dispersed in anhydrous ethanol, and hexamethyldisilazane (CAS: 999-97-3, purchased from Aladdin Reagents (Shanghai) Co., Ltd.) was added. The mixture was stirred and refluxed at 80℃ for 6h, centrifuged, washed, and vacuum dried to obtain alkylated SiO2 with a surface free energy ≤25mN / m.
[0070] Example 1
[0071] Preparation of battery separator
[0072] (1) Preparation of coating slurry A
[0073] Weigh 50g of PVDF-HFP and dissolve it in 300g of N-methylpyrrolidone (NMP). Stir at 60℃ for 4 hours to form a transparent solution. Add 50g of nanoparticles A (nano-garnet type LLZTO, D... 50 =350nm), stirred at 5000rpm for 2h in a high shear disperser, and then vacuum degassed for 1h to obtain coating slurry A.
[0074] (2) Preparation of coating slurry B
[0075] Weigh 30g of PVDF-HFP and dissolve it in 420g of NMP, then add 30g of pre-modified functional particles B (fluorinated Al2O3, D). 50 =100nm) and 35g functional particles A (nano LLZTO, D) 50=350nm), after high-speed dispersion for 2 hours, add 25g of deionized water as a pore-forming agent and continue stirring for 30 minutes, then degas for 1 hour to obtain coating slurry B.
[0076] (3) Coating and curing
[0077] On the same continuous coating production line, coating slurry A is coated on one side of a 9μm thick PE base film (facing the negative electrode side) by a gravure roller, with a wet film thickness of about 3μm. The film is then dried in an 80℃ oven for 0.5h to set. Subsequently, a second gravure roller coats coating slurry B on the formed coating A, and the wet film thickness is stacked to about 4μm to obtain a composite film.
[0078] The composite membrane was placed in a segmented temperature-controlled oven: in the first temperature zone (pre-drying / setting zone), it was heated to 60°C for 60 seconds, and then in the second temperature zone (complete drying zone), it was heated to 80°C and air-dried for 2 minutes. Afterward, it was wound up to obtain the battery separator. The total dry thickness of the single-sided coating of this battery separator is approximately 3.5 μm (the thickness of the bottom coating A is approximately 1.4 μm, and the thickness of the top coating B is approximately 2.1 μm). The pore size of coating B is 147 nm, and the pore size of coating A is 36 nm.
[0079] Example 2
[0080] The method is the same as in Example 1, except that the nano-LLZTO in the two slurries is replaced by an equal weight of nano-lithium aluminum titanium phosphate (LATP, D) 50 =120nm); a battery separator with a total thickness of approximately 3.4μm on one side was obtained (the thickness of the bottom coating A is approximately 1.5μm, and the thickness of the top coating B is approximately 1.9μm). The pore size of coating B is 152nm, and the pore size of coating A is 38nm.
[0081] Example 3
[0082] A multifunctional gradient coating was applied to both sides of the PE base film using a stepwise continuous coating method. The coating facing the negative electrode side was prepared according to the double-layer slurry formulation and process of Example 1.
[0083] The coating facing the positive electrode side omits functional particle B, retaining only the modified ceramic and the substrate to improve pressure resistance and oxidation resistance.
[0084] Coating paste A' is the same as coating paste A;
[0085] Preparation of coating slurry B'
[0086] Weigh 30g of PVDF-HFP and dissolve it in 420g of NMP and 35g of functional particles A (nano LLZTO, D). 50 =350nm), after high-speed dispersion for 2 hours, add 25g of deionized water as a pore-forming agent and continue stirring for 30 minutes, degas for 1 hour, and obtain coating slurry B'.
[0087] Coating and curing
[0088] The coating method for the negative electrode side is the same as in Example 1. The intermediate separator is formed by winding. The coating method for the separator facing the positive electrode side is as follows: On the same continuous coating production line, coating slurry A' is coated on one side of the intermediate separator (facing the positive electrode side) by a gravure roller. The wet film thickness is about 3 μm. It is then dried in an oven at 80°C for 0.5 h until it is set. Then, a second gravure roller coats coating slurry B' on the formed coating A', and the wet film thickness is about 4 μm to obtain a composite film.
[0089] The composite membrane was placed in a segmented temperature-controlled oven: in the first temperature zone (pre-drying / setting zone), it was kept at 60°C for 60 seconds, and then in the second temperature zone (complete drying zone), the temperature was increased to 80°C and air-dried for 2 minutes. The membrane was then wound up to obtain the battery separator. The total dry thickness of the single-sided coating on the positive electrode side of this battery separator is approximately 3.5 μm (the thickness of the bottom coating A is approximately 1.4 μm, and the thickness of the top coating B' is approximately 2.1 μm). The pore size of coating A and coating B' is the same, both being 147 nm. The thickness and pore size of the separator on the negative electrode side are the same as in Example 1.
[0090] Example 4
[0091] The method is the same as in Example 1, except that the fluorinated Al2O3 in coating slurry B is replaced by an equal weight of alkylated SiO2 (D). 50 (≈100nm), resulting in a battery separator with a total thickness of approximately 3.4μm on one side (bottom coating thickness A is approximately 1.4μm, and top coating thickness B is approximately 2μm). The pore size of coating B is 145nm, and the pore size of coating A is 38nm.
[0092] Example 5
[0093] Following the method of Example 1, except that the fluorinated Al2O3 in the surface coating slurry B was replaced by an equal weight of PTFE (100 nm), resulting in a battery separator with a total dry thickness of approximately 3.4 μm on one side (the bottom coating A is approximately 1.5 μm thick, and the top coating B is approximately 1.9 μm thick). The pore size of coating B is 142 nm, and the pore size of coating A is 37 nm.
[0094] Example 6
[0095] The method is the same as in Example 1, except that the amounts of polymer matrix and nanoparticles A in the undercoat slurry A are as follows:
[0096] Weigh 70g of PVDF-HFP and dissolve it in 300g of N-methylpyrrolidone (NMP). Stir at 60℃ for 4 hours to form a transparent solution; add 30g of nanoparticles A (nano-garnet type LLZTO, D... 50=350nm), stirred at 5000rpm for 2h in a high-shear disperser, and then vacuum degassed for 1h to obtain the bottom coating slurry A.
[0097] The final battery separator has a total thickness of approximately 3.4 μm on one side (the bottom coating A has a thickness of approximately 1.5 μm, and the top coating B has a thickness of approximately 1.9 μm). The pore size of coating B is 140 nm, and the pore size of coating A is 32 nm.
[0098] Example 7
[0099] The method is the same as in Example 1, except that the amounts of polymer matrix and nanoparticles A in the undercoat slurry A are as follows:
[0100] Weigh 90g of PVDF-HFP and dissolve it in 300g of N-methylpyrrolidone (NMP). Stir at 60℃ for 4 hours to form a transparent solution. Add 10g of nanoparticles A (nano-garnet type LLZTO, D... 50 =350nm), stirred at 5000rpm for 2h in a high-shear disperser, and then vacuum degassed for 1h to obtain the bottom coating slurry A.
[0101] The final battery separator has a total thickness of approximately 3.4 μm on one side (bottom coating A is approximately 1.4 μm thick, and top coating B is approximately 2 μm thick). The pore size of coating B is 145 nm, and the pore size of coating A is 25 nm.
[0102] Example 8
[0103] The method is the same as in Example 1, except that the amounts of polymer matrix, nanoparticles B, solvent, pore-forming agent, and nanoparticles A in the surface coating slurry B are as follows:
[0104] Weigh 50g of PVDF-HFP and dissolve it in 450g of NMP, then add 30g of pre-modified functional particles B (fluorinated Al2O3, D). 50 =100nm) and 35g functional particles A (nano LLZTO, D) 50 =350nm), after high-speed dispersion for 2 hours, add 25g of deionized water as a pore-forming agent and continue stirring for 30 minutes, degas for 1 hour, and obtain surface coating slurry B.
[0105] The final battery separator has a total thickness of approximately 3.4 μm on one side (bottom coating A is approximately 1.4 μm thick, and top coating B is approximately 2 μm thick). The pore size of coating B is 124 nm, and the pore size of coating A is 39 nm.
[0106] Example 9
[0107] The method is the same as in Example 1, except that the amounts of polymer matrix, nanoparticles B, solvent, pore-forming agent, and nanoparticles A in the surface coating slurry B are as follows:
[0108] Weigh 20g of PVDF-HFP and dissolve it in 360g of NMP, then add 30g of pre-modified functional particles B (fluorinated Al2O3, D). 50 =100nm) and 35g functional particles A (nano LLZTO, D) 50 =350nm), after high-speed dispersion for 2 hours, add 25g of deionized water as a pore-forming agent and continue stirring for 30 minutes, degas for 1 hour, and obtain surface coating slurry B.
[0109] The final battery separator has a total thickness of approximately 3.4 μm on one side (bottom coating A is approximately 1.5 μm thick, and top coating B is approximately 1.9 μm thick). The pore size of coating B is 174 nm, and the pore size of coating A is 37 nm.
[0110] Example 10
[0111] The method is the same as in Example 1, except that nanoparticles A are not used in the surface coating slurry B. Instead, nanoparticles A are replaced by nanoparticles B at the same weight, as detailed below:
[0112] Weigh 30g of PVDF-HFP and dissolve it in 420g of NMP. Add 65g of pre-modified functional particles B (fluorinated Al2O3, D) 50 =100nm), after high-speed dispersion for 2 hours, add 25g of deionized water as a pore-forming agent and continue stirring for 30 minutes, degas for 1 hour, and obtain surface coating slurry B.
[0113] The final battery separator has a total thickness of approximately 3.4 μm on one side (bottom coating A is approximately 1.4 μm thick, and top coating B is approximately 2 μm thick). The pore size of coating B is 143 nm, and the pore size of coating A is 38 nm.
[0114] Example 11
[0115] The method is the same as in Example 1, except that the 9μm thick PE base film is replaced with a 9μm thick PE / PP / PE three-layer composite film.
[0116] The final battery separator has a total thickness of approximately 3.4 μm on one side (bottom coating A is approximately 1.5 μm thick, and top coating B is approximately 1.9 μm thick). The pore size of coating B is 143 nm, and the pore size of coating A is 36 nm.
[0117] Example 12
[0118] The method is the same as in Example 1, except that the 9μm thick PE base film is replaced with a 5μm thick PE base film.
[0119] The final battery separator has a total thickness of approximately 3.4 μm on one side (bottom coating A is approximately 1.4 μm thick, and top coating B is approximately 2 μm thick). The pore size of coating B is 148 nm, and the pore size of coating A is 37 nm.
[0120] Example 13
[0121] The method is the same as in Example 1, except that the 9μm thick PE base film is replaced with a 12μm thick PE base film.
[0122] The final battery separator has a total thickness of approximately 3.4 μm on one side (bottom coating A is approximately 1.5 μm thick, and top coating B is approximately 1.9 μm thick). The pore size of coating B is 147 nm, and the pore size of coating A is 35 nm.
[0123] Example 14
[0124] The method is the same as in Example 1, except that the thicknesses of the bottom coating A and the top coating B are changed so that the thickness ratio of the base film, the bottom coating A, and the top coating B is 1:0.11:0.28.
[0125] The final battery separator has a total thickness of approximately 3.5 μm on one side (bottom coating A is approximately 1 μm thick, and top coating B is approximately 2.5 μm thick). The pore size of coating B is 142 nm, and the pore size of coating A is 36 nm.
[0126] Example 15
[0127] The method is the same as in Example 1, except that the thicknesses of the bottom coating A and the top coating B are changed so that the thickness ratio of the base film, the bottom coating A, and the top coating B is 1:0.28:0.11.
[0128] The final battery separator has a total thickness of approximately 3.5 μm on one side (bottom coating A is approximately 2.5 μm thick, and top coating B is approximately 1 μm thick). The pore size of coating B is 145 nm, and the pore size of coating A is 34 nm.
[0129] Example 16
[0130] The method is the same as in Example 1, except that the average particle size D of nanoparticles A in coating slurry A and coating slurry B is different. 50 All are 250 nm. In coating slurry B, the average particle size D of nanoparticles B is... 50 It is 50nm.
[0131] The final battery separator has a total thickness of approximately 3.4 μm on one side (bottom coating A is approximately 1.4 μm thick, and top coating B is approximately 2 μm thick). The pore size of coating B is 132 nm, and the pore size of coating A is 28 nm.
[0132] Example 17
[0133] The method is the same as in Example 1, except that the average particle size D of nanoparticles A in coating slurry A and coating slurry B is different. 50 The average particle size D of nanoparticles B in coating slurry B is 500 nm. 50 It is 200nm.
[0134] The final battery separator has a total thickness of approximately 3.4 μm on one side (bottom coating A is approximately 1.4 μm thick, and top coating B is approximately 2 μm thick). The pore size of coating B is 168 nm, and the pore size of coating A is 47 nm.
[0135] Comparative Example 1
[0136] Dissolve 40g of PVDF-HFP in 400g of NMP, and add 60g of conventional high-purity nano-alumina (D2HFP) without any surface modification. 50 =100nm), without adding solid electrolyte or water, high-speed dispersion for 2 hours and degassing for 1 hour; coated on one side of a 9μm PE base film, without humidity control (no segmented temperature control), directly dried at 80℃ for 3 minutes. A conventional ceramic membrane with uniform pores, no gradient, and no low surface energy anti-adsorption properties on the inner wall was obtained, with a dry thickness of 3.5μm.
[0137] Comparative Example 2
[0138] Slurries A and B were prepared according to the stepwise continuous coating process and polymer ratio of Example 1. All inorganic particles in slurries A and B were replaced with unmodified conventional nano-alumina (without perfluoroalkyl linkages and without LLZTO). All other preparation conditions were the same as in Example 1.
[0139] Coating paste A''
[0140] Weigh 50g of PVDF-HFP and dissolve it in 300g of N-methylpyrrolidone (NMP). Stir at 60℃ for 4h to form a transparent solution. Stir at 5000rpm for 2h using a high-shear disperser and degas under vacuum for 1h to obtain coating slurry A''.
[0141] Coating paste B''
[0142] Weigh 30g of PVDF-HFP and dissolve it in 420g of NMP. Add 30g of granular B (conventional Al2O3, D) 50 =100nm), after high-speed dispersion for 2 hours, add 25g of deionized water as a pore-forming agent and continue stirring for 30 minutes, degas for 1 hour, and obtain coating slurry B''.
[0143] The remaining preparation process is the same as in Example 1, resulting in a double-layer gradient separator with gradient pore size but no anti-fouling capability on the pore walls and no backup lithium conduction path, with a dry thickness of 3.6 μm. The pore size of coating B is 140 nm, and the pore size of coating A is 38 nm.
[0144] Comparative Example 3
[0145] Using the same modified Al2O3 and LLZTO formulation and ratio as in Example 1, but with all components mixed into a single homogeneous slurry, coated once with a single die (without a second coating or introducing a pore size gradient), and directly dried at 80°C for 3 min, a composite diaphragm with uniform pore size and no pore size gradient was obtained, with a dry thickness of 3.5 μm. This was used to independently verify the independent contribution of the gradient pore structure to long-cycle compression resistance.
[0146] The coating slurry is as follows:
[0147] Weigh 80g of PVDF-HFP and dissolve it in 720g of N-methylpyrrolidone (NMP). Stir at 60℃ for 4 hours to form a transparent solution; add 85g of nanoparticles A (nano-garnet type LLZTO, D... 50 =350nm) and 30g of pre-modified functional particles B (fluorinated Al2O3, D 50 =100nm), and stirred at 5000rpm for 2h in a high shear disperser. Then, 25g of deionized water was added as a pore-forming agent and stirring was continued for 30min. Vacuum degassing was carried out for 1h to obtain coating slurry A.
[0148] Test case
[0149] The separators prepared in the above embodiments and comparative examples were assembled into high-energy-density ternary / graphite system soft-pack batteries (3Ah). Long-term cycle tests were conducted at 25°C with 1C charge / 1C discharge (1C charge and 1C discharge constitute one cycle). The batteries were disassembled at cycle 0 (before cycling) and cycle 1000 (after cycling), the separators were cleaned and the air permeability was measured. At the same time, the lithium deposition on the negative electrode surface was observed. No lithium deposition was recorded as no lithium deposition, and lithium deposition was recorded as lithium deposition.
[0150] The test method for diaphragm air permeability is as follows:
[0151] The test was conducted in accordance with the requirements of GB / T36363—2018 "Polyolefin Separators for Lithium-ion Batteries". A 600mm × 100mm coated battery separator sample was cut and tested using a Wangyan-type air permeability meter (ASAHI Corporation, EG01-55-1MR). The test time was 3 seconds. The air permeability of the battery separator was measured at arbitrary positions at 100mm intervals along the 600mm TD direction. The average value of the above 5 test points was recorded as the air permeability of the battery separator.
[0152] Wherein, the capacity retention rate after 1000 cycles = discharge capacity of the 1000th cycle / discharge capacity of the first cycle × 100%.
[0153] .
[0154] Data results statement:
[0155] (1) Excellent pore anti-fouling and anti-compression ability: After 1000 long cycles, the change ratio of air permeability B / A in Examples 1 to 18 was strictly controlled below 1.2, proving that the synergistic design of "physical repulsion" and "dynamic ion flow reconstruction" was successful and effectively prevented channel clogging and compression closure; while the air permeability of Comparative Example 1 increased by 3.3 times, indicating that the pores were seriously clogged by side reaction products.
[0156] (2) The necessity of synergistic effect between particle modification and structure: Although Comparative Example 2 has gradient pores, it lacks the physical repulsion of low surface energy perfluoroalkyl chains and the source reduction of LLZTO, and the air permeability value still deteriorates by 2.4 times after cycling; Comparative Example 3 has modified particles and LLZTO but no gradient structure, and the B / A ratio still reaches 1.69. Both sets of comparisons prove that the gradient structure and the modified functional particle group are indispensable and must work together to achieve the antifouling effect of B / A≤1.2.
[0157] (3) Thoroughly suppressing lithium plating on the negative electrode and improving lifespan: Due to the highly stable permeability (B / A≤1.2) during long-term cycling, the lithium-ion transport network inside the separator is not damaged, achieving a long-term uniform distribution of ion flow and fundamentally suppressing lithium plating on the negative electrode. The embodiments of the present invention retain more than 88.5% capacity after 1000 cycles, and the preferred embodiments can achieve more than 92% capacity with no obvious lithium plating on the negative electrode, significantly extending the working life of the battery under harsh operating conditions.
[0158] It should be noted that the embodiments described above are only for explaining the present invention and do not constitute any limitation on the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory terms, not limiting terms. Modifications can be made to the present invention within the scope of the claims, and revisions can be made to the present invention without departing from the scope and spirit of the present invention. Although the present invention described herein relates to specific methods, materials, and embodiments, it does not mean that the present invention is limited to the specific examples disclosed herein; on the contrary, the present invention can be extended to all other methods and applications with the same function.
Claims
1. A battery separator, the battery separator comprising a base film and a multifunctional gradient coating formed on at least one surface of the base film, wherein, The multifunctional gradient coating comprises a stacked bottom coating A and a top coating B, wherein the bottom coating A contains solid ionic conductor nanoparticles A, the top coating B contains nanoparticles B, and the pore size of the top coating B is larger than that of the bottom coating A; the nanoparticles B are inorganic particles and / or polymer microparticles with low surface energy.
2. The battery separator according to claim 1, characterized in that, The particle size of nanoparticle A is larger than that of nanoparticle B; preferably, the average particle size D of nanoparticle A is... 50 The nanoparticles are 250nm-500nm in size; preferably, the average particle size D of the nanoparticles B is... 50 100nm-200 nm; And / or, the nanoparticle A is selected from garnet-type solid electrolytes and / or NASICON-type solid electrolytes; preferably, the nanoparticle A is selected from one or more of LLZTO, LATP, and LAGP; And / or, the surface free energy of the nanoparticle B is ≤25 mN / m; Preferably, the nanoparticles B are selected from one or more of fluorinated or alkylated Al2O3, fluorinated or alkylated SiO2, fluorinated or alkylated TiO2, PTFE-based microparticles, fluorinated polyether microparticles, and fluorinated or alkylated ZrO2.
3. The battery separator according to claim 1 or 2, characterized in that, The bottom coating A contains a first polymer matrix and nanoparticles A; Preferably, based on the total weight of the bottom coating A, the content of the first polymer matrix is 50-90% by weight, and the content of nanoparticles A is 10-50% by weight. Preferably, the first polymer matrix is selected from one or more of polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride, polyacrylonitrile, and polyacrylic acid resin.
4. The battery separator according to any one of claims 1-3, characterized in that, The surface coating B contains a second polymer matrix, nanoparticles B, and optional nanoparticles A; Preferably, based on the total weight of the surface coating B, the content of the polymer matrix is 20-50% by weight, the content of nanoparticles B is 20-70% by weight, and the content of nanoparticles A is 0-45% by weight. Preferably, the second polymer matrix is selected from one or more of polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride, polyacrylonitrile, and polyacrylic acid resin.
5. The battery separator according to any one of claims 1-4, characterized in that, Based on the total weight of the battery separator, the total content of the first polymer matrix and the second polymer matrix is 30-50% by weight, the content of nanoparticle B is 10-40% by weight, the content of nanoparticle A is 20-50% by weight, and the content of nanoparticles in the surface coating B is greater than the content of nanoparticles in the bottom coating A. Preferably, the weight ratio of nanoparticle B to nanoparticle A is 1:0.5-3; Preferably, the thickness ratio of the base film, the bottom coating A, and the top coating B is 1:0.1-0.5:0.1-0.
7.
6. The battery separator according to any one of claims 1-5, characterized in that, The base film is a wet-process biaxially oriented polyethylene single-layer film or a PE / PP / PE multilayer composite film; preferably, the thickness of the base film is 5μm-12μm.
7. The battery separator according to any one of claims 1-6, characterized in that, The change ratio of the air permeability value B of the battery separator after 1000 1C charge / 1C discharge cycles to the air permeability value A of the battery separator before the cycles is B / A≤1.
2.
8. A method for preparing the battery separator according to any one of claims 1-7, the method comprising: S1. Apply the undercoating slurry A to at least one surface of the base film and perform a first drying to obtain a base film with the undercoating A. S2. Apply a topcoat slurry B to the surface of the base film with the bottom coating A obtained in S1, and perform a second drying. Preferably, the first drying conditions include: a temperature of 50-90°C and a time of 0.2-2 hours; and / or, the second drying conditions include: raising the temperature to 50-70°C, holding for 30-120 seconds, and then raising the temperature to 70-90°C and holding for 1-5 minutes.
9. The method according to claim 8, characterized in that, The underlying coating slurry A contains a first polymer matrix, nanoparticles A, solvent A, and optional pore-forming agent A; preferably, the weight ratio of the first polymer matrix, nanoparticles A, solvent A, and optional pore-forming agent A is 1:0.1-12:3-10:0-0.
3. And / or, the surface coating slurry B contains a second polymer matrix, nanoparticles B, solvent B, pore-forming agent B, and optional nanoparticles A; preferably, the weight ratio of the second polymer matrix, nanoparticles B, solvent B, pore-forming agent B, and optional nanoparticles A is 1:0.5-3:3-20:0.3-1.5:0-3.
10. A battery comprising the battery separator of any one of claims 1-7 and / or the battery separator prepared by the method of any one of claims 8-9.
Citation Information
Patent Citations
Conductive ceramic composite separator and solid-state battery
CN108878751B
